IMPLEMENTASI PROGRAM ASI EKSKLUSIF SEBAGAI INTERVENSI GIZI SPESIFIK DALAM GERAKAN 1000 HARI PERTAMA KEHIDUPAN DI KOTA DEPOK 2020 - Audry (2021)
Depok exclusive breastfeeding prevalence only reached 66.4%, the lowest was in Cipayung District at 59.2%, which is below the minimum health service standard of 80%. This study aims to determine the implementation of the EBF program and use it as a specific nutrition intervention in the first 1000 days of life movements in Depok City 2020. The research is a descriptive qualitative method through in-depth interviews and observations. The research informants consisted of the Head of Nutrition District at Depok Health Office, Head of Cipayung Health Center, nutritionist, midwives, cadre, and breastfeeding mother. The results showed that the implementation of the program was not optimal. In the aspect of disposition, comprehension, response and commitment were good. There was a data gap in an integrated data collection system in a bureaucratic structure. Resources which are breastfeeding counselors are limited, several public places don't have nursing rooms, and a diverted budget for Covid-19. Pandemic and lack of public awareness are obstacles to communication. The EBF program in the first 1000 days of life movement was implemented in Depok. Suggestions for the Health Office are centralized data collection and optimization of resource procurement, for PHC are policy socialization and tasks delegation also active community participation.